1999
DOI: 10.5694/j.1326-5377.1999.tb123822.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobile intensive care services in rural South Australia

Abstract: Synopsis In the years from to 1995, Adelaide‐based mobile intensive care teams transported 4443 critically ill patients from rural areas in South Australia and adjacent States to tertiary‐level hospitals in Adelaide. The SA Ambulance Service undertook communications, support staffing and deployment of transport. Average radial distances in 819 road missions were 71 km, in 808 helicopter missions 122 km, and in 2777 fixed‐wing aircraft missions 398 km. The largest groups of patients were neonates (23%) and tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…The principal finding of this study is that most patients with severe traumatic brain injury in Northern Norway undergo air transport and that via this approach it is possible to achieve short inter-hospital transfer times despite extremely long geographical distances. This is in accordance with experience from other rural regions of the world (Rogers et al, 1999;Gilligan et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…The principal finding of this study is that most patients with severe traumatic brain injury in Northern Norway undergo air transport and that via this approach it is possible to achieve short inter-hospital transfer times despite extremely long geographical distances. This is in accordance with experience from other rural regions of the world (Rogers et al, 1999;Gilligan et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…This study found that the death rate in transport for critically ill patients was 1%, compared to 2.5% in South Australia, and 4% in the UK and Canada (33)(34)(35). This low rate may be a direct reflection of the quality of in-transit care provided as described above, notwithstanding the selfselection bias inherent in any service that has prolonged response times due to the geography and logistics surrounding the extensive distances involved and the use of fixedwing aircraft, which require linking road transport.…”
Section: Discussionmentioning
confidence: 73%
“…2,15,[29][30][31][32][33] Even with specialist mobile intensive care teams, mortality before and during transport is substantial (2.5%) despite a low incidence of preventable deaths during transport (0.02% to 0.04%). 2,15,[29][30][31][32][33] Even with specialist mobile intensive care teams, mortality before and during transport is substantial (2.5%) despite a low incidence of preventable deaths during transport (0.02% to 0.04%).…”
Section: Adverse Effectsmentioning
confidence: 99%